Characterization of informal caregivers of older adults in COVID-19 pandemic situation in Tamaulipas, Mexico - Cuevas-Martinez, Karla Iris (Universidad de Sonora, 2022)
Introduction: COVID-19 mitigation measures increased the need for informal caregiving among older adults; characterizing caregivers will enable the development of strategies to support caregivers during the contingency. Objective: To describe the socio-demographic and health characteristics of informal caregivers of older adults, aspects of caregiving, and access to technology during the COVID-19 pandemic. Methodology: Cross-sectional descriptive study of 52 informal caregivers identified by snowball sampling. Unpaid caregivers over 18 years of age were included. Data were collected online, using a specially designed data form. Frequencies, percentages and measures of central tendency were calculated. Results: 67% were women, married (36%), Catholics (73.1%), with an average age of 37 years and 13 years of schooling. Thirty-six percent were engaged in the home and 21.2% were students. Seventy-three percent did not suffer from chronic diseases and slept 7 hours a day, dedicating 9.4 hours a day to care for people. Care by children predominated in 35%, who did not live with the older adult (54%), sharing the care with other people in 83%, 79% had no training and only 21.2% received training by nurses. 63% received information on COVID-19 prevention and 96% had internet at home. Conclusions: The informal caregiver is characterized by women with an average age of 37 years, high schooling and apparently healthy; which require guidance by nurses to perform care during the contingency.